Analysis of the productive chain profile of the red ceramics industry (RCI) regarding climate change in the metropolitan region of Cariri, Ceará - Oliveira, Petrônio Silva de; Oliveira, Ulisses Costa de; Feitosa, Carlos Eduardo Linhares; Florêncio, Maria Magnólia Batista (Revista Hipótese, 2018)
This work aimed to analyze the profile of the Red Ceramic Industry (ICV) production chain, in Cariri metropolitan region, Ceará. To it, a data collection was elaborated from the year 2011 to 2014 in companies that develop productive processes of ICV, covering aspects of location and environmental situation, qualification of the decision makers, knowledge about the National Policy of Climate Change and the Kyoto Protocol, the existence of actions that would promote the neutralization of emissions, knowledge of the ceramics about their greenhouse gas (GHG) emissions and benefits that the neutralization of GHG emissions would bring in decision makers perspective. The results showed that the ceramic industries are concentrated in the municipality of Crato, which accounts for 57.14% of the total number of ceramics licensed in the region. Most of the ceramics analyzed are in operation, accounting for 74.07% with a valid operating license. Most of the decision makers have a higher education, representing 55% of the total analyzed, between undergraduate and specialization, which could point to a good knowledge of the causes related to global warming and the worsening of the Greenhouse Effect (EE) and desertification of the Caatinga. Regarding the decision-makers' knowledge about possible actions on climate change, 95% of companies managers were unaware of the issue. As for the actions that would promote the neutralization of emissions, 33.33% of the managers stated that they do not know and 27.78% did not have an action, project or program to reduce their emissions. Regarding the Quito Protocol, 42.86% still do not know it and 28.57% have only a superficial view of this important pact in mitigating the worsening of the EE. Finally, according to the interviewees, the benefits are directly related to the ecological issue (64%), to the detriment of other issues, such as social (4.00%) and economic (20%).
Keywords: Ceramics; Greenhouse gases; Climate changes